Realistic Mathematics Learning Strategies in Mathematics to Introduce Beginning On a Group of Children in Kindergarten the Ananda Kudus - Andriyani, Lisa; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2016)
The childs readiness for entering primary education is characterized by the development of all the potential of the child. One of the potential that needs to be developed early on was the base for the preparation of skills in reading, writing and counting. On the cognitive field is the addition of knowledge into long-term memory therefore age 4-5 years children can get knowledge about simple concepts in everyday life today, as does the math to know the beginning. In Indonesia, learning counting can be taught on children provided in accordance with tahapanya and methods used should be fun, realistic mathematics learning strategies could be options of teachers to introduce children in the learning of mathematics in particular the introduction of the basic concept of the symbol number. This study aims to describe the application of learning strategies in realistic mathematics introduces math beginning in children.This study is a qualitative research approach with the approach of case studies and using the method of observation, interviews, and documentation in and gather data. Technique of data analysis research is Miles: with Huberman& presentation data, reduction of data, summary and verification.The research results showed that introducing math commencement through learning strategies in realistic mathematics done in kindergarten the include Ananda Kudus planning learning strategy, organizing, delivery strategies, and management strategies. Introducing mathematics beginning kindergarten teacher AnandaKudus one of them invites children to play traditional games, traditional games with children indirectly learning about the introduction of the concept. So child-centered learning and the teacher is a facilitator for the children, where the main activities facilitate teacher needed by the child. The main activities will be explained by teachers in the delivery of the material to the next teacher freed children to perform the play. Teachers evaluate the child by means of observation during the activities of the main and petrified children when children have difficulty in completing the game activities.